Pneumothorax in SARS-CoV-2 Affected Patients - Srivatsa, R.; Hosmane, Giridhar Belur; Venkataram, Rajesh; Baikunje, Nandakishore (Journal of Health and Allied Sciences NU, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has various known complications in its natural course of the illness. Pneumothorax is one of the emerging complications in coronavirus disease 2019 (COVID-19)-positive patients, not initiated on invasive mechanical ventilation. Case studies and autopsy reports across the globe suggest alveolar pathology to be responsible for the outcome.COVID-19 infection in humans caused by the SARS-CoV-2 virus has various known complications in its natural course of the illness. Pneumothorax is one of the emerging complications in COVID-19-positive patients. Prior identification and anticipation of such life-threatening complications aid in the treatment of COVID-19-positive patients.
Keywords: pneumothorax; SARS-CoV-2; mechanical ventilation; complications